Trends in obesity and associations with education and Urban or rural residence in Thailand - Aekplakorn W. (2014)
Objective: To measure trends in the prevalence of over-weight and obesity and the relationship with urban or rural residence and education in Thailand. Research Methods and Procedures: Data were from two nationally representative surveys of 38,323 individuals ≥18 years old (19,156 were 18 to 59 years old) in 2004 and 3375 individuals 18 to 59 years old in 1997. Overweight and obesity were defined using the World Health Organization's Asian criteria. Results: Among those ≥18 years old in 2004, 17.8% of men (95% confidence interval, 16.6% to 19.0%) were over-weight, 18.4% (17.3% to 19.5%) had Class I obesity, 4.8% (4.1% to 5.5%) had Class II obesity, and 15.9% (14.6% to 17.1%) had abdominal obesity. In women, 18.2% (17.1% to 19.2%) were overweight, 26.1% (24.9% to 27.3%) had Class I obesity, 9.3% (8.6% to 10.0%) had Class II obesity, and 37.3% (35.3% to 39.2%) had abdominal obesity. In those 18 to 59 years old, the prevalence of Class I obesity in men and all four categories in women significantly increased between 1997 and 2004. There was an inverse relationship in women but a positive relationship in men between education and the odds of being overweight or obese. In 2004, there were significantly lower odds of being overweight or obese in rural compared with urban men but similar odds between urban and rural women. Discussion: The prevalence of overweight and obesity in Thailand is high and increasing. Although the transition of overweight and obesity to those of lower socioeconomic status is not complete, it is well on the way. Copyright © 2007 NAASO.